B-Raf inhibitor vemurafenib counteracts sulfur mustard-induced epidermal impairment through MAPK/ERK signaling. (4th March 2023) - Xiao, Zhiyong; Liu, Feng; Cheng, Junping; Wang, Ying; Zhou, Wenxia; Zhang, Yongxiang
Abstract: The chemical warfare agent sulfur mustard (SM) causes severe cutaneous lesions characterized by epidermal cell death, apoptosis, and inflammation. At present, the molecular mechanisms underlying SM-induced injury are not well understood, and there is no standard treatment protocol for SM-exposed patients. Here, we conducted a high-content screening of the Food and Drug Administration (FDA)-approved drug library of 1018 compounds against SM injury on an immortal human keratinocyte HaCaT cell line, focusing on cell survival. We found that the B-Raf inhibitor vemurafenib had an apparent therapeutic effect on HaCaT cells and resisted SM toxicity. Other tested B-Raf inhibitors, both type-I (dabrafenib and encorafenib) and type-II (RAF265 and AZ628), also exhibited potent therapeutic effects on SM-exposed HaCaT cells. Both SM and vemurafenib triggered extracellular signal-related kinase (ERK) activation. The therapeutic effect of vemurafenib in HaCaT cells during SM injury was ERK-dependent, indicating a specific role of ERK in keratinocyte regulatory mechanisms. Furthermore, vemurafenib partially improved cutaneous damage in a mouse ear vesicant model. Collectively, our results provide evidence that the B-Raf inhibitor vemurafenib is a potential therapeutic agent against SM injury, and oncogenic B-Raf might be an exciting new therapeutic target following exposure to mustard vesicating agents.